2016
DOI: 10.1007/s10753-016-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Attenuates Lipopolysaccharide-Induced Acute Kidney Injury by Inhibiting TLR4/NF-κB Signal Pathway

Abstract: Chlorogenic acid (CGA), a polyphenolic compound, exists widely in medicinal herbs, which has been shown a strong antioxidant and anti-inflammatory effect. This study investigated the protective effects and mechanism of CGA on lipopolysaccharide (LPS)-induced acute kidney injury (AKI). Treatment of CGA successfully ameliorates LPS-induced renal function and pathological damage. Moreover, CGA dose-dependently suppressed LPS-induced blood urea nitrogen (BUN), creatinine levels, and inflammatory cytokines TNF-α, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 16 publications
3
59
0
1
Order By: Relevance
“…observed that inhibition of TLR4/NF‐κB pathway could reduce inflammatory response and urine derived sepsis‐induced kidney injury. Lipopolysaccharide is a classical ligand for TLR4 that can activate TLR4‐/NF‐κB signaling pathway in acute kidney injury mice, which leads to the increase of inflammatory cytokine, such as interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) . PTEN also involved in LPS induced proinflammatory cytokine production .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…observed that inhibition of TLR4/NF‐κB pathway could reduce inflammatory response and urine derived sepsis‐induced kidney injury. Lipopolysaccharide is a classical ligand for TLR4 that can activate TLR4‐/NF‐κB signaling pathway in acute kidney injury mice, which leads to the increase of inflammatory cytokine, such as interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) . PTEN also involved in LPS induced proinflammatory cytokine production .…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide is a classical ligand for TLR4 that can activate TLR4-/NF-jB signaling pathway in acute kidney injury mice, which leads to the increase of inflammatory cytokine, such as interleukin-6 (IL-6) and tumor necrosis factor-a (TNF-a). [12] PTEN also involved in LPS induced proinflammatory cytokine production. [13] Therefore, PTEN and TLR4/NF-jB pathway play important role in urine derived sepsis-induced kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that CGA protects against vital organ injury, such as acute liver and acute kidney injury, by inhibiting inflammasome activation. 18,19 The present study showed that CGA significantly improved vascular leakage in septic shock rats, then enhanced tissue perfusion in vital organs including the heart, and thus improved hemodynamic status and survival time. Improvement in the endothelial barrier by CGA was closely related to increased expression of ZO-1 and VEcadherin.…”
Section: Discussionmentioning
confidence: 52%
“…C-QA protects liver and kidney injury in mice caused by D-galactose, due to C-QA's antioxidation and anti-inflammation effects (110). C-QA also attenuates AKI caused by LPS by inhibiting the TLR4/NF-κB signaling pathway (107). The results of this study indicated that C-QA decreased LPS-induced kidney damage by suppressing oxidative stress, inflammation, apoptosis and autophagy, enhancing kidney regeneration (111).…”
Section: Polyphenols Microbiota and Ckdmentioning
confidence: 68%